Capillary Refill—The Key to Assessing Dermal Capillary Capacity and Pathology in Optical Coherence Tomography Angiography. Issue 7 (21st November 2019) - Casper, M. J.; Glahn, J.; Evers, M.; Schulz‐Hildebrandt, H.; Kositratna, G.; Birngruber, R.; Hüttmann, G.; Manstein, D.
Abstract : Background/Objectives: Standard optical coherence tomography angiography (OCTA) has been limited to imaging blood vessels actively undergoing perfusion, providing a temporary picture of surface microvasculature. Capillary perfusion in the skin is dynamic and changes in response to the surrounding tissue's respiratory, nutritional, and thermoregulatory needs. Hence, OCTA often represents a given perfusion state without depicting the actual extent of the vascular network. Here we present a method for obtaining a more accurate anatomic representation of the surface capillary network in human skin using OCTA, along with proposing a new parameter, the Relative Capillary Capacity (RCC), a quantifiable proxy for assessing capillary dilation potential and permeability. Methods: OCTA images were captured at baseline and after compression of the skin. Baseline images display ambient capillary perfusion, while images taken upon capillary refill display the network of existing capillaries at full capacity. An optimization‐based automated vessel segmentation method was used to automatically analyze and compare OCTA image sequences obtained from two volunteers. RCC was then compared with visual impressions of capillary viability. Results: Our OCTA imaging sequence provides a method for mapping cutaneous capillary networks independent of ambient perfusion. Differences between baseline and refill images clearly demonstrate the shortcomings of standard OCTA imaging and produce the RCC biometric as a quantifiable proxy for assessing capillary dilation potential and permeability. Conclusion: Future dermatological OCTA diagnostic studies should implement the Capillary Refill Methods over standard imaging techniques and further explore the relevance of RCC to differential diagnosis and dermatopathology. Lasers Surg. Med. © The Authors. Lasers in Surgery and Medicine published by Wiley Periodicals, Inc.